Pengaruh Pajak Reklame terhadap Pendapatan Asli Daerah Kota Kupang - Sanggo, Veren; Dhiu, Mitha; Bunga, Enjel; Mali Loe, Priska; Lawalu, Emiliana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research investigates the influence of advertisement tax on the Local Own-Source Revenue (PAD) of Kupang City over the period from 2020 to 2024. As part of the regional tax system, advertisement tax contributes to the financing of regional development through the local government budget (APBD). While its share is relatively minor when compared to other local taxes such as those from restaurants, hotels, and parking, the advertisement tax still holds an important role in funding public services and infrastructure. The study employs a descriptive quantitative approach, with data gathered through interviews and official documents from the Regional Revenue Agency (BAPENDA) of Kupang City. The research focuses on comparing the annual targets and actual revenues from advertisement tax, as well as its contribution to overall PAD. The results show a fluctuating pattern in advertisement tax revenue, with the highest collection achieved in 2020 at 105.64% of the target, and the lowest in 2022 at only 54.28%. In 2024, the revenue reached around 66.9% of the planned target. Although inconsistent, advertisement tax remains a key element in supporting critical sectors such as education, healthcare, environmental sanitation, public infrastructure, and government operations. The study concludes that improving the management and enforcement of advertisement tax backed by firm regulations and effective oversight can increase its contribution to PAD and enhance the financial autonomy of the region.